EFEKTIVITAS SANKSI DEWAN KEAMANAN PERSERIKATAN BANGSA-BANGSA TERHADAP KONFLIK BERSENJATA DI SURIAH - Teddy Nurcahyawan; Lauw Wisnu (Faculty of Law - Tarumanagara University, 2018)
As a soverign state in the Middle East, Syria has received badly effect of Arab Spring revolution. Thousand of students launched demonstration claiming Bashar Al-Assad to step down. In response to it, Bashar Al-Assad attacked the prodemocracy students by arresting and torturing them. This arms conflict has not only brought many civilians as victims of civil war but involved some other foreign states as well. To avoid matters worse, Security Council of United Nations has issued a Resolution Number 2328/2016 to give sanctions affirming Bashar-Assad to have violated international humanitarian law. The question comes up whether or not this resolution could present the effectiveness of the sanctions. This research has revealed that the Security Council Resolution is effective and Syria has complied with it in line with the international law.